Hubungan Pemberian ASI Eksklusif Dan Paparan Asap Rokok Dengan Status Gizi Baduta Di Kecamatan Muntilan Kabupaten Magelang - Fauzia Liesly Anindya; Ruri Trisasri; Fia Mifta Amin (Universitas Ivet, 2025)
Nutritional problems in children under two years old (toddlers) are an important issue in public health in Indonesia. This study aims to analyze the relationship between exclusive breastfeeding and exposure to cigarette smoke with the nutritional status of toddlers aged 1–6 months in the working area of Muntilan District, Magelang Regency, in 2025. The study used a quantitative design with a cross-sectional approach, involving 124 mothers and 56 toddlers. Data were collected through secondary data and anthropometric measurements based on indicators of BB/U and PB/U according to WHO 2006 standards. Analysis was carried out univariately and bivariately using the Chi-square test. The results showed that 89.5% of mothers provided exclusive breastfeeding and 57.3% of toddlers were exposed to cigarette smoke at home. Most toddlers had normal nutritional status (BB/U: 83.9%; PB/U: 80.4%). Bivariate testing showed no significant relationship between exclusive breastfeeding and nutritional status (weight/age p = 0.642; height/age p = 0.711) or between cigarette smoke exposure and nutritional status (weight/age p = 0.483; height/age p = 0.520). Although not statistically significant, these findings emphasize the importance of healthy parenting behaviors and a smoke-free home environment to support the growth of toddlers.